Fracture simulation parameters of fractured reservoirs: Analogy with outcropping carbonates of the Inner Apulian Platform, southern Italy. (June 2019) - Giuffrida, Alessandro; La Bruna, Vincenzo; Castelluccio, Paola; Panza, Elisa; Rustichelli, Andrea; Tondi, Emanuele; Giorgioni, Maurizio; Agosta, Fabrizio
Abstract: This work focuses on the nature, relative timing, and multi-scale dimensional properties of both background and fault-related fracture networks that crosscut the Lower Cretaceous shallow-water carbonates exposed at the Monte Alpi, southern Italy. Away from the major fault zones, fractures mainly consist of stratabound and non-stratabound joints and sheared joints, which form two main bed-perpendicular cross-orthogonal sets. Both sets are characterized by a Poissonian spacing distribution, they do not form well-defined clusters, and formed during either burial diagenesis or subsequent Upper Miocene foreland flexure of the Inner Apulian Platform. In contrast, the study fault damage zone is mainly crosscut by non-stratabound fractures and through-going slip surfaces, which form clustered conjugate systems characterized by power law spacing distributions. Results of Discrete Fracture Network modelling of geocellular volumes representative of the surveyed outcrops show that the fractured carbonates of the study fault damage zone form the main storage volume for underground fluids. There, non-stratabound fractures act as the main control on fracture porosity and contribute towards determining isotropic horizontal fluid flow properties. These isotropic conditions are interpreted as a factor of the profound control exerted by the pre-existing cross-orthogonal fracture sets, which underwent to an extreme uplift during the Plio-Quaternary tectonic evolution of the area. Data presented in this work also highlight the importance of scan area methods for the quantitative analysis of stratabound fracture sets. Highlights: Dimensional and scalar properties of both background and fault-related fracture networks are computed. Both scanline and scanarea methods are employed for quantitative fracture analysis. Values of fracture porosity and permeability for host rock dependent upon the methods employed for structural analysis. Values of fracture porosity and permeability for the fault damage zone are not dependent from the methods employed in field. Fault damage zones, characterized by quite isotropic horizontal flow properties, form main repositories for underground fluids.